Elimination of NF-κB signaling in Vimentin+ stromal cells attenuates tumorigenesis in a mouse model of Barrett's Esophagus. (17th October 2020) - Anand, Akanksha; Fang, Hsin-Yu; Mohammad-Shahi, Donja; Ingermann, Jonas; Baumeister, Theresa; Strangmann, Julia; Schmid, Roland M; Wang, Timothy C; Quante, Michael
Abstract: Chronic inflammation induces Barrett's Esophagus (BE) which can advance to esophageal adenocarcinoma. Elevated levels of interleukin (IL)-1b, IL-6 and IL-8 together with activated nuclear factor-kappaB (NF-κB), have been identified as important mediators of tumorigenesis. The inflammatory milieu apart from cancer cells and infiltrating immune cells contains myofibroblasts (MFs) that express aSMA and Vimentin. As we observed that increased NF-κB activation and inflammation correlates with increased MF recruitment and an accelerated phenotype we here analyze the role of NF-κB in MF during esophageal carcinogenesis in our L2-IL-1B mouse model. To analyze the effect of NF-κB signaling in MFs, we crossed L2-IL-1B mice to tamoxifen inducible Vim-Cre (Vim-CreTm) mice and floxed RelA (p65 fl/fl ) mice to specifically eliminate NF-κB signaling in MF (IL-1b.Vim-CreTm.p65 fl/fl ). The interaction of epithelial cells and stromal cells was further analyzed in mouse BE organoids and patient-derived human organoids. Histological scoring of IL-1b.Vim-CreTm.p65 fl/fl mice showed a significantly attenuated phenotype compared with L2-IL-1B mice, with mild inflammation, decreased metaplasia and no dysplasia. This correlated with decreased proliferation and increased differentiation in cardia tissue of IL-1b.Vim-CreTm.p65 fl/fl compared with L2-IL-1B mice. Distinct changes of cytokines and chemokines within the local microenvironment in IL-1b.Vim-CreTm.p65 fl/fl mice reflected the histopathological abrogated phenotype. Co-cultured NF-κB inhibitor treated MF with mouse BE organoids demonstrated NF-κB-dependent growth and migration. MFs are essential to form an inflammatory and procarcinogenic microenvironment and NF-κB signaling in stromal cells emerges as an important driver of esophageal carcinogenesis. Our data suggest anti-inflammatory approaches as preventive strategies during surveillance of BE patients. Abstract : In a mouse model of esophageal carcinogenesis activated stromal cells such as myofibroblast are important for tumor progression. Elimination of NF-κB expression in myofibroblasts attenuates tumor development, suggesting a role for anti-inflammatory preventive strategies during surveillance.